(untitled) (Olhar de Professor, 2021)
This study focuses on early childhood education in the context of a pandemic caused by Covid-19, since much has been seen and discussed about this stage, with distance teaching activities being a factor of concern by researchers and educators from early childhood. It is characterized as a qualitative and as a documentary case study and aims to briefly present and discuss some aspects of the implementation of a municipal Educational Program, created in a pandemic context, showing possibilities of work, but also some limits and challenges. The data indicate strategies and tools that enabled the continuity of links between schools, teachers, children and families, as well as the continuity of the teachers’ work. It is also inferred the need for constant evaluation of actions and proposals linked to this Program, aiming at being intentional, effective and not excluding, guaranteeing the educational rights of babies and children, even in such a complex, urgent and unprecedented scenario. Keywords: early childhood education, pandemic by Covid-19, pedagogical activities at a distance